Tissue characterization using mean gray value analysis in deep infiltrating endometriosis. (25th March 2013) - Guerriero, S.; Pilloni, M.; Alcazar, J. L.; Sedda, F.; Ajossa, S.; Mais, V.; Melis, G. B.; Saba, L.
ABSTRACT Objectives To investigate differences in tissue characterization using three‐dimensional sonographic mean gray value (MGV) between retrocervical and rectosigmoid deeply infiltrating endometriosis, and to assess intra‐ and interobserver concordance in MGV quantification. Methods In this retrospective study, stored ultrasound volumes from 50 premenopausal women (mean age, 32 years) with 57 histologically confirmed nodules of deep endometriosis were retrieved from our database for analysis. A single experienced operator had acquired all volumes. For each nodule, the MGV was evaluated using Virtual Organ Computer‐aided AnaLysis (VOCAL) software with semiautomated sphere‐sampling (1 cm3) from the central part of the nodule. In these patients the MGV was also quantified from the myometrium of the fundal part of the uterus. In addition, two observers calculated the MGV in a subset of 24 volumes in order to quantify inter‐ and intraobserver agreement using intraclass correlation coefficients (ICC). Results Mean MGV was significantly higher in rectosigmoid nodules (n = 34) than in nodules with a retrocervical location (n = 23) (23.863 vs 17.705; P < 0.001). MGV of the myometrium was significantly higher in comparison with that of nodules in both locations (P < 0.001 for both). Intra‐ and interobserver measurement reproducibility was excellent (ICC > 0.95). Conclusions Retrocervical and rectosigmoid endometriotic nodules display significantly different MGVs. Measurement of MGV is highly reproducible and its clinical value in the diagnosis and assessment of distribution of deep endometriosis should be assessed in future studies. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.